Cyber Threats in Hybrid Warfare: A Strategic Mapping and Response Framework for National Defense - Shoraya Lolyta Octaviana; Totok Imam Santoso; Zainal Abidin Sahabuddin; Guntur Eko Saputro (Yayasan Sembilan Pemuda Indonesia, 2026)
Hybrid warfare integrates military and non-military instruments, with cyberspace emerging as a critical domain. Cyber threats in this context are systemic, multidimensional, and difficult to attribute, yet existing studies often treat cybersecurity and hybrid warfare separately. This study maps cyber threats within hybrid warfare frameworks and formulates strategic responses to support national defense. A qualitative descriptive approach was used, combining systematic literature review (45 peer-reviewed articles and policy documents, 2018–2025), Soft System Methodology (SSM) for complexity analysis, and SWOT analysis for strategic formulation. Four principal cyber threat types were identified: attacks on critical infrastructure, cyber espionage, disinformation campaigns, and influence operations. Key characteristics include multidimensionality, attribution difficulty, asymmetry, and involvement of both state and non-state actors. SSM revealed interconnected systems across technology, governance, and society. SWOT analysis identified strengths (growing digital human resources) and weaknesses (limited inter-agency coordination). A strategic response model comprising system integration, capacity enhancement, and national coordination is proposed. National defense systems must adopt holistic, adaptive frameworks that integrate cyber capabilities, cross-sectoral collaboration, and societal resilience. Future research should empirically test the proposed model in national defense contexts.